[Untitled article] - Gagné, Jean-H. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1952)
SummaryThe awards studied under this heading were rendered during the months of November and December of last year and January and February of this year. An outline of the points which we found to be of the most interest in these awards follows, under the various subjects covered.